DIGITAL LITERACY WITH EFL STUDENTS: DISCOVERING BANTEN’S STUDENTS' PERCEPTION ABOUT INTEGRATING DIGITAL TECHNOLOGIES IN COLLABORATIVE LEARNING - Azra Nur Izzati Aziz; Kheryadi Kheryadi (Universitas Wiralodra, 2024)
This research aims to investigates Bantenese students' perceptions of integrating digital technologies in collaborative learning. A descriptive qualitative approach was engaged, employing questionnaires as the primary means of data collection. Subsequently, the data underwent a comprehensive analysis involving data reduction, presentation, and the formulation of conclusions. The research revealed that the integration of technology in collaborative learning, from the viewpoint of Bantenese’ students, offers substantial support and benefits to both educators and learners. It provides convenient access to comprehensive information from various reputable sources, thereby reducing the time needed for assignments. Nonetheless, a drawback associated with the incorporation of technology in education is the risk of fostering passivity in students, as they may opt for immediate solutions through artificial intelligence or turn to assignment service websites, raising concerns about their authenticity and data security. This research also underscores the necessity for additional exploration into the difficulties encountered by students in Banten when engaging in collaborative learning approaches that incorporate technology.